Exploring Ethnoscience through Dodol Pangi: Context-Based Learning in the Soppeng Community - Imranah; Andi Sitti Aisyah; Elvira (Postgraduate, University of Mataram, 2026)
This study aims to explore the scientific concepts embedded in the traditional production of dodol pangi (Pangium edule) in the Soppeng community, South Sulawesi, and to examine its potential as a context for integrating ethnoscience into science learning. Using a qualitative ethnographic design, data were collected through participatory observation, in-depth interviews, and documentation involving eight purposively selected informants. Analysis followed Miles and Huberman’s interactive model, revealing key scientific mechanisms embedded in each production stage, including detoxification through leaching and diffusion, heat and mass transfer, starch gelatinization, Maillard reactions, and retrogradation during cooling. The results show that the stages of boiling, washing, soaking, cooking, and cooling reflect empirically grounded scientific processes that are consistently applied by the community in producing dodol pangi. These findings indicate that traditional knowledge is not merely cultural practice, but also represents contextual scientific understanding that can be meaningfully connected to formal science concepts in learning. These findings demonstrate how local wisdom reflects contextual scientific principles relevant to everyday practices. In conclusion, the dodol pangi tradition has strong potential to serve as a meaningful context for ethnoscience-based science learning that supports scientific literacy and appreciation of local wisdom.